South China Sea : Beijing's 'Salami Slicing' strategy - Darshana M. Baruah (2014)
The South China Sea is seeing increasing tension amongst the claimants. The Second Thomas Shoal is the latest addition to Beijing’s ‘Salami Slicing’ strategy of slowly acquiring small reefs and islands to consolidate its contested claim.